Wartości uniwersalne i narodowe w konstytucjach schyłku XVIII wieku - Libiszowska, Zofia (Acta Universitatis Lodziensis. Folia Historica, 1995)
Three constitutions, the American (1787-1789), the French (1791) and the Polish (3 May 1791) have a similar ancestry. They were born in the atmosphere of changes and revolutions, whose inspirations was the political thought of the European Enlightenment (from Locke and Montesquieu to Jean Jacques Rousseau) and the ideas of the rights of man, which were already partly realized in England. The author notes the theoretical foundations, and the appeal to the will of society (in „We, the Poeple” ) in the preambles and preliminary declarations of these constitutions. The passing of all three constitutions was accompanied by a veritable pamphlet and propaganda war. The constitution of the United States, as the first of the three, and first in the world, influenced the concepts of the other two, and inspired the national liberation movements in South America and Europe against foreign rule. The American example was always lively in Poland. The constitutions sanctioned breaks with the old regime, considered to be the accumulated evil of centuries. They created societies of citizens, and proclaimed religions toleration and the rights of the individual. No less important, however, are the differences between the constitutions arising from varying international situations and social expectations. The United States, having won independence as 13 free republics, built the structure of a federal state. As a result of revolution, France created a new system of power based on the equality and liberty of all citizens. Poland, threatened after the first partition, tried to save the state through a constitution which redefined the stage as the common property of all its inhabitants by breaking in some way the social banners of estates. The Poles attempted to rescue their independence. All the constitutions were met by reaction and criticism, which in France and Poland led to foreign intervention. France saved itself but at the price of the terror. After military defeat, the Polish constitution fell, but it left a legand, and contributed to the rebirth o f the Polish nation in the nieneteenth century.